From Bean to Cup: Assessing the Effectiveness of a Coffee Processing Module - Colis, Lemuel; Domingo, Cyril John (Journal of Interdisciplinary Perspectives, 2025)
Specialty coffee processing is an area of growing educational significance. This study developed and evaluated a specialty coffee processing module for high school students enrolled in the Technical-Vocational-Livelihood (TVL) strand in Palimbang District, Sultan Kudarat. Using a quantitative, descriptive-evaluative approach, the research assessed the module's effectiveness based on student learning, engagement, and satisfaction. Results showed a significant increase in student knowledge, with post-test scores (40.22 ± 5.06) surpassing pre-test scores (16.19 ± 5.13), resulting in a mean difference of 24.03 and a retention rate of 71.08%. Expert evaluations rated the module high quality across all factors, with an average score of 3.83 out of 4.0, particularly excelling in accuracy and reliability (4.00 ± 0.00). Student satisfaction levels were also notably high, with an overall mean score of 4.60 ± 0.38, suggesting a very high extent of quality relevance. These results indicate that integrating specialty coffee processing education into vocational training can enhance student learning outcomes and engagement, supporting its inclusion in future curricula.